Microwave-assisted deep eutectic solvents/dimethyl sulfoxide system for efficient valorization of sugar bagasse waste into platform chemicals: A biorefinery approach for circular bioeconomy. (November 2022) - Amesho, Kassian T.T.; Cheng, Pei-Cheng; Chang, Ken-Lin; Peng, Yen-Ping; Jhang, Syu-Ruei; Lin, Yuan-Chung
Graphical abstract: Highlights: MW-mediated DESs/DMSO system was developed for the production platform chemicals. SB as an agro-waste material can be exploited as feedstock for platform chemicals. The yields for 5-HMF, FF and LA reached 31.29%, 28.38% and 35.65%, respectively. The Arrhenius diagram results indicated an activation energy ( Ea ) of 29.11 kJ/mol. Favorable results were achieved at the reaction temperature of 140 °C for 40 min. Abstract: The exploitation of lignocellulosic biomass (LB) such as sugar bagasse waste in biorefineries is the most cost-effective and favourable sustainable approach to producing essential platform chemicals, materials, and energy environmentally benignly. Herein, a microwave-mediated deep eutectic solvents (DESs)/dimethyl sulfoxide (DMSO) system for efficiently processing LB waste into platform chemicals was proposed thereof. Under optimized appropriate diverse parameters such as solvent varieties, catalyst dosage, DMSO addition, reaction time and temperature, the proposed catalytic system (i.e., microwave mediated DESs/DMSO system) has demonstrated significant yields of 5-hydroxymethylfurfural (5-HMF), furfural (FF) and levulinic acid (LevA) of 31.29 %, 28.38 % and 35.65 %, respectively. These favourable results were obtained at the reaction temperature of 140 °C for 40 min. The anticipated catalytic system's activation energy ( Ea ) was found to be 29.11 kJ/mol. Hence, a practical, inexpensive and sustainable process with the potential of high-value platform chemicals, explicitly for a sustainable strategy in a circular bioeconomy was proposed.